Desarrollo del proceso de modelación matemática en licenciados en formación (2021)
For authors such as Blum, Galbraith, Henn and Niss (2007), modeling has its starting point in the conceptualization of a situation or problem of reality. For Blum and Borromeo-Ferri (2009), this process is schematized in a cycle that has certain phases that allow an adequate reasoning of the modeling problems. This article proposes a cycle based on these authors and in the studied context of the graduates in training of the Universidad del Atlántico, after which a contrast is made between the proposed cycle and the processes that students develop when they solve a problem mathematical modeling raised from experimentation.